Journal of Psychological Volume 13, Number 2, July-December 2023 - Arias Gallegos, Walter L. (2024)
At the beginning of the 20th century, when modern psychology was taking its first           steps      of        institutionalization          in            Argentina,           in            an           increasingly        secularized          world,    it        seemed  that        science  excluded               any         possibility            of            relationship        with        the        religious               field.      However,              a             new         program               of            scientific              psychology        was        organized             in the heart of Catholicism in Europe and spread in the Americas as far as Argentina.        What     did          it             contribute            to            the          nascent local      psychology?        This        paper        describes intellectual migrations in the circulation of psychological knowledge and practices linked to the international Catholic movement known as Neo-Scholasticism.               These     migrations          are          recorded        during   the          process of            institutionalization of Argentine psychology as a science and profession between the  1900s     and         1960s.    Institutions         and         university             training programs,            as            well        as        travels,  disciple relationships,     and         reference               publications        are          highlighted.         The        global view reveals that, beyond a common philosophical base, a heterogeneity of psychological knowledge and practices was disseminated, consistent with the             breadth of            academic             trajectories,         as           well        as           political orientations.       However,              a              uniform pattern  seems    to            have       been        followed                in            the          promotion           of            a             scientific              culture that would support an autonomous psychology as a science and profession,             based     on           an           integral vision     of            the        object    of            study.